Thinning or dehiscence of bone in structures of the middle cranial fossa floor in superior semicircular canal dehiscence. (April 2020) - Arsenault, John J.; Romiyo, Prasanth; Miao, Tyler; Monteiro, Kristina; De Jong, Russell; Kaur, Taranjit; Johanis, Michael; Duong, Courtney; Sheppard, John P.; Sun, Matthew Z.; Ferraro, Regan; Salamon, Noriko; et al.
Highlights: Superior semicircular canal dehiscence is an uncommon ear disorder. SSCD is correlated with higher rates of geniculate ganglion dehiscence and thinning. Increased salience of MCF dehiscence in SSCD patients compared to non-SSCD patients. MCF thinning is more amplified in bilateral SSCD patients. Abstract: Background: Superior semicircular canal dehiscence (SSCD) is a rare inner ear disorder; currently, it is unknown whether the etiopathology underlying this structural irregularity affects neighboring structures. The goal is to investigate the prevalence of bone thinning in areas of the middle cranial fossa (MCF) floor in SSCD and non-SSCD patients. Methods: This retrospective study analyzed 100 patients from March 2011 to June 2017 at a tertiary referral center. 100 patients undergoing 118 SSCD repair surgeries (18 bilateral) were identified. 12 SSCD ears were excluded due to lack of pre-operative computed tomography (CT) scans or history of prior SSCD repair at an outside facility. Non-SSCD ears were identified from routinely-obtained CT scans for temporal bone fracture (fractured sides excluded) for a total of 101 ears; 26 non-SSCD ears were excluded due to lack of high-resolution imaging. Results: Univariate analyses reveal that SSCD diagnosis is associated with higher rates of geniculate ganglion (GG) dehiscence compared with non-SSCD controls (42.7 vs. 24%; χ 2 (1) = 9.69, P = 0.008). Individuals with SSCD depicted significantly thinner bone overlying the geniculate ganglion (GG) (0.23 ± 1.2 mm) compared to controls (0.28 ± 1.8 mm, (t(1 6 4)) = 2.1, P = 0.04). SSCD patients presented thinner bone overlying the internal auditory canal (IAC) (0.33 ± 1.3 mm) compared to patients without SSCD (0.46 ± 1.6 mm, (t(2 5 7) = 6.4, P < 0.001). Conclusions: The increased prevalence of dehiscence of the MCF in this cohort of SSCD patients compared to non-SSCD patients suggests that the etiology underlying SSCD affects surrounding structures.